Effect of inactivated COVID-19 vaccination on intrauterine insemination cycle success: A retrospective cohort study - Xu, Zijin; Wu, Yixuan; Lin, Yanshan; Cao, Mingzhu; Liang, Zhu; Li, Lei; Lin, Jiali; Chen, Qian; Liu, Jianqiao; Liu, Haiying (Frontiers in Public Health, 2022)
Background: Vaccine hesitancy was found in couples seeking artificial reproductive technology (ART) services. As the main vaccine used in China, investigations into the influence of inactivated coronavirus disease 2019 (COVID-19) vaccines on human fertility is needed. Methods: This retrospective cohort study included data on COVID-19 vaccination, clinical characteristics, and reproductive outcome of 1000 intrauterine insemination(IUI) cycles in 653 couples from March 2021 to March 2022 in a single university hospital-based center for reproductive medicine. The IUI cycles were divided into two categories based on sperm source, including 725 cycles in 492 women undergoing artificial insemination with their husband's sperm (AIH) and 275 cycles in 161 women undergoing artificial insemination with donor sperm (AID). Women were then divided into two groups. The vaccine exposed group included women vaccinated prior to insemination and the unexposed group included women who were not vaccinated or vaccinated after insemination. Reproductive outcomes including ongoing pregnancy rate, clinical pregnancy rate, and miscarriage rate were assessed. Results: Inactivated COVID-19 vaccinated women prior to intrauterine insemination in AIH cycles have comparable ongoing pregnancy rate (11.1% vs. 10.3%, P = 0.73), clinical pregnancy rate (12.5% vs. 11.3%, P = 0.60) as compared with unvaccinated counterparts. Similarly, there were no significant differences in ongoing pregnancy rate (20.9% vs. 28.1%, P = 0.17), clinical pregnancy rate (21.7% vs. 28.8%, P = 0.19) between vaccine exposed and unexposed groups in AID cycles. Multivariable logistic regression analyses showed that inactivated COVID-19 vaccination status cannot independently influence the reproductive outcomes of AIH and AID cycles. Subgroup analysis of vaccine exposed cycles showed that doses of vaccination and Interval between the last dose of vaccination and insemination have no influence on the reproductive outcomes of AIH cycles. Conclusions: No negative effects were found on female fertility in IUI cycles following exposure to the inactivated COVID-19 vaccine. These findings indirectly reflect the safety of inactivated COVID-19 vaccine towards reproductive health and help to mitigate vaccine hesitancy among people planning to conceive.